PERBANDINGAN KADAR FLAVONOID EKSTRAK ETANOL DAUN KELENGKENG (Dimocarpus logan L.) DENGAN VARIASI METODE EKSTRAKSI - Zaldy Rusli; Yulianita Yulianita; Elfrida Erawati Sitanggang (EKOLOGIA, 2022)
Longan plants (Dimocarpus logan L.) are generally used by the community only for their fruit. Longan leaves contain secondary metabolites such as flavonoids, polyphenols, saponins, and tannins. Flavonoids are polyphenolic compounds and have antioxidant properties that are not heat-resistant, therefore a suitable method is needed for extracting flavonoids, especially methods that do not use heat. Maceration extraction method is an extraction method by immersing simplicia at room temperature, while the Microwave Assisted Extraction (MAE) extraction method is an extraction method using microwave radiation. The study aims to determine the most effective method for flavonoid content of longan leaves using 2 extraction methods, namely maceration and MAE. Determination of flavonoid content was done using Aluminium chloride reagent whose absoption was measured using UV-Vis spectrophotometry. The results showed that the best extraction method to produce the highest flavonoid content in 70% ethanol extract of longan leaves was the Microwace Assisted Extraction method which produced flavonoid levels of 1.32 ± 0,09%.